Metal–Salen‐Incorporated conjugated microporous polymers as robust artificial leaves for solar‐driven reduction of atmospheric CO2 with H2O - Wei Wu; Zhaocen Dong; Mantao Chen; Waner Li; An Liao; Qing Liu; Yachao Zhang; Zhixin Zhou; Chao Zeng; Xuezhong Gong; Chunhui Dai (Carbon Energy)
Abstract Exploration of efficient and stable photocatalysts to mimic natural leaves for the conversion of atmospheric CO2 into hydrocarbons utilizing solar light is very important but remains a major challenge. Herein, we report the design of four novel metal–salen‐incorporated conjugated microporous polymers as robust artificial leaves for photoreduction of atmospheric CO2 with gaseous water. Owing to the rich nitrogen and oxygen moieties in the polymeric frameworks, they show a maximum CO2 adsorption capacity of 46.1 cm3 g−1 and adsorption selectivity for CO2/N2 of up to 82 at 273 K. Under air atmosphere and simulated solar light (100 mW cm−2), TEPT‐Zn shows an excellent CO yield of 304.96 μmol h−1 g−1 with a selectivity of approximately 100%, which represents one of the best results in terms of organic photocatalysts for gas‐phase CO2 photoreduction so far. Furthermore, only small degradation in the CO yield is observed even after 120‐h continuous illumination. More importantly, a good CO yield of 152.52 μmol g−1 was achieved by directly exposing the photocatalytic reaction of TEPT‐Zn in an outdoor environment for 3 h (25–28°C, 52.3 ± 7.9 mW cm−2). This work provides an avenue for the continued development of advanced polymers toward gas‐phase photoconversion of CO2 from air.